2019
DOI: 10.5935/1980-6906/psicologia.v21n1p170-185
|View full text |Cite
|
Sign up to set email alerts
|

Parents seeking a diagnosis of Autism Spectrum Disorder for their child

Abstract: Sistema de avaliação: às cegas por pares (double blind review). Universidade Presbiteriana Mackenzie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Participants reported that they were the first to identify the symptoms. This matches the findings of Xavier et al [17], but is in sharp contrast to those by Sicherman et al [24], who claimed that the earliest signs were perceived by acquaintances, friends, or the extended family in half of the cases. A possible explanation may lie in the parents' greater capacity to detect the initial symptoms, either because the children with ASD had no siblings and may have received more attention from their parents, or because they had older siblings whose development served as a reference.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Participants reported that they were the first to identify the symptoms. This matches the findings of Xavier et al [17], but is in sharp contrast to those by Sicherman et al [24], who claimed that the earliest signs were perceived by acquaintances, friends, or the extended family in half of the cases. A possible explanation may lie in the parents' greater capacity to detect the initial symptoms, either because the children with ASD had no siblings and may have received more attention from their parents, or because they had older siblings whose development served as a reference.…”
Section: Discussionsupporting
confidence: 90%
“…Following an apparently normal development period, family members and those closest to them begin to identify certain behaviors that differ from the usual development patterns around the child's first or second year of life [16]. Symptoms such as a tendency to social isolation, a lack of communicative intent, the rejection of emotional contact, and some stereotypical behaviors can lead the family to seek health professional support as they start to become aware of the disorder [17]. Throughout this process, parents usually begin to feel a certain degree of frustration and helplessness, especially because of the length of time between initial concerns being noted and the final diagnosis being received [14].…”
Section: Waiting For the Diagnosismentioning
confidence: 99%
See 1 more Smart Citation